Islamic-Informed Self-Compassion as a Protective Mechanism against Negative Body Image: A Phenomenological Study of Female Adolescents in Islamic Schools - Khotimah, Dewi Fitriah Khusnul; Shobahiya, Mahasri; Hafidz, Hafidz (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study aims to: (1) analyze the role of self-compassion in dealing with negative body image and the factors influencing it among female adolescents; (2) explore the contribution of moral education to the development of self-compassionate attitudes; and (3) evaluate the impact of self-compassion on the psychological and social well-being of female adolescents in Islamic schools. This research addresses the limitations of previous studies, which predominantly employed quantitative approaches and have not contextually addressed spiritual values. Design/methods/approach – This study employed a qualitative approach with a phenomenological design. Four female adolescents from Muhammadiyah Junior High Schools 7 and 8 in Surakarta were purposively selected based on their experiences with negative body image. Data were collected through semi-structured interviews, participatory observation, and document studies, and analyzed using Miles and Huberman’s technique. Data validity was enhanced through triangulation of methods, sources, and theories. Findings – The study found that self-compassion functions as a protective mechanism that helps female adolescents manage social pressures related to the body. The three main dimensions of Neff’s framework—self-kindness, common humanity, and mindfulness—were identified in the participants’ narratives. Moral education that internalizes Islamic values such as gratitude (syukur), contentment (qanaah), and sincerity (ikhlas) contributed to self-acceptance and psychological resilience. Self-compassion also had a positive impact on increasing self-confidence, emotional calmness, and healthy social relationships. Research implications – The findings recommend a reformulation of the Islamic Religious Education curriculum to be more responsive to adolescents’ psychosocial issues, as well as the development of spiritual mentoring programs and Islamic media literacy to promote positive body image and emotional well-being among students.